STRATEGI MENINGKATKAN KINERJA MENGGUNAKAN PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA, BEBAN KERJA, DAN KOMPENSASI PADA KARYAWAN DINAS PETERNAKAN DAN PERIKANAN KABUPATEN GROBOGAN - Sugiyanti Sugiyanti; Darmadi Darmadi (Riset Manajemen dan Akuntansi, 2020)
The study purposes were determined the effect of work environment, work discipline, workload and compensation on employee’s performance at the Department of Animal Husbandry and Fisheries Grobogan Regency either partially or simultaneously. The research type was used quantitative data with a population of 62 respondents. Data collection techniques were used observation, interviews and distributing questionnaires. The data analysis technique were used multiple linear regression, t test, f test and coefficient of determination. The research results showed that the work environment, work discipline, workload, and compensation have positive and significant effect on employee performance. The work environment is the most dominant variable on employee performance, so the Department of Animal Husbandry and Fisheries of Grobogan Regency needs to maintain air conditions, noise intensity and room coloring, if necessary, create a work atmosphere capable of providing comfort to employees while working.